Ação antidumping: produção de camarão em cativeiro e desenvolvimento regional na microrregião do litoral de Aracati CE - Alves, Antonio Kaminski (2012)
This study aims at analyzing the impacts of the antidumping action imposed to Brazilian shrimp farmers by the North-American fishing industry, as well as its effects on the economic development of the Microregion Coast of Aracati (Ceará, Brazil), from 2003 to 2010. It is an exploratory research in conformity with the theoretical and methodological framework presented in Lüdke and André (1986). The research sought to highlight facts of reality through representative samples of the three links of the production chain of shrimp grown in captivity, namely: a) laboratories/hatcheries; b) shrimp farms; c) the processing industry/exporter. For field research, the questionnaire was chosen as an instrument of data collection, and four types of questionnaires were developed and submitted. With regard to the bibliography, theoretical support was sought in the field s literature, reference works, dissertations and theses, scientific papers, official texts of antidumping legislation, and research on sites of WTO and other national and international institutions. In this study, two forms of analysis and interpretation of facts and figures were used: firstly, a qualitative analysis was carried out for the interpretation of the phenomena focused in the investigated object; secondly, a quantitative test was done by calculating the location quotient LQ, with the use of the methodology proposed by Hildebrand and Mace (1950). The study presents a mapping of the aquaculture in Ceará based on data collection of formal employment at RAIS. The analysis of the collected data evidenced the features of the shrimp farming in the Microregion Coast of Aracati (Ceará), and regarding the antidumping action, it was found that it is a factor that interferes with the development of shrimp farming. Concerning the perspectives for the sector, three challenges that require special attention are described: a) implementation of policies to support large enterprises and social inclusion policies, with the incorporation of the small farmer to the activity; b) support to inland shrimp farming with the shrimp L. vannamei, adapted to the reservoir waters and perennial rivers; c) consolidation of public bodies concerning the sector, such as the Ministry of Fisheries and Aquaculture (MFA) and the Law of Fishing and Aquaculture, as well as the creation of the new Forest Code. In addition, it is noteworthy the foundation of Embrapa Aquaculture, in the context of the Law that created the MFA, unfolding a new perspective on the generation and distribution of technologies for the Brazilian aquaculture industry.